Screaming silences. Screen Memories and Postmemories of the Resistance and the Shoah in two French Contemporary Novels - Vanassche, Tom (Status Quaestionis, 2020)
If the memory of the anti-fascist Resistance has served as a screen memory for collaboration and colonial violence, recent postmemories and the polemical debates they arouse are equally marked by telling silences. In this article, I analyse two contemporary French novels in which the memories of the Resistance and of the Shoah are entangled: Laurent Binet’s HHhH and Yannick Haenel’s Jan Karski. Nevertheless, these novels and the polemics in which they find themselves are still riddled with screaming silences concerning collaboration. These questions will be discussed alongside the novels’ conscious use of fictionality as a metacommentary on processes of commemoration.